Nexus Sekuritisasi Kesehatan dan Komunikasi Kesehatan di Masa Pandemi - Prasojo, Prasojo (Jurnal Keamanan Nasional, 2022)
This article performs a descriptive analysis of the relationship between health securitization and health communication. The pandemic situation is a test for securitizing actors to be able to apply appropriate securitization strategies to referent objects for mutual safety. But one thing that cannot be done is to predict when the pandemic will end. Eventually, this becomes a long-term game that requires adaptive health communication strategies. Health securitization during a pandemic requires the application of a health communication strategy that can maintain the trust of the referent object so that the securitizing actor’s efforts to return the situation to normal.